1994
DOI: 10.1177/104063879400600114
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Maternal and Fetal Liver Copper, Iron, Manganese, and Zinc Concentrations and Fetal Development in California Holstein Dairy Cows

Abstract: Abstract. Associations between maternal trace element deficiencies and abortion have been made for many mammalian species. Objectives of this study were to estimate and correlate maternal and fetal hepatic Cu, Fe, Mn, and Zn concentrations through gestation. Additionally, aborted fetuses, stratified by cause of abortion (infectious or noninfectious), were compared to size-matched nonaborted fetuses to examine for magnitude and direction of change in hepatic trace element status. Dam and fetal liver were remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 38 publications
1
22
0
2
Order By: Relevance
“…While (Graham et al, 1994) found that maternal liver Cu was not correlated with fetal size. Fetal liver Cu increased as fetal age increased and was less than to maternal Cu in early gestation and there was no differences between maternal and fetal liver Cu in late gestation, while fetal liver Cu was significantly higher than that of the maternal liver through gestation (Gonneratne and Christensen, 1989a), as well as Cu concentration was significantly increased in early gestation than that of late gestation in the fetal liver (Abdelrahman and Kincaid, 1993) and kidney while (Richards, 1999) found that in fetal kidney, Cu concentration did not change significantly with gestation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While (Graham et al, 1994) found that maternal liver Cu was not correlated with fetal size. Fetal liver Cu increased as fetal age increased and was less than to maternal Cu in early gestation and there was no differences between maternal and fetal liver Cu in late gestation, while fetal liver Cu was significantly higher than that of the maternal liver through gestation (Gonneratne and Christensen, 1989a), as well as Cu concentration was significantly increased in early gestation than that of late gestation in the fetal liver (Abdelrahman and Kincaid, 1993) and kidney while (Richards, 1999) found that in fetal kidney, Cu concentration did not change significantly with gestation.…”
Section: Discussionmentioning
confidence: 90%
“…Ovine maternal and fetal liver Cu were negatively correlated in this and previous reports (Gonneratne and Christensen, 1989a). Presence of significant negative relationship between age of the fetus and maternal liver Cu concentration as well as the relationships between maternal liver and amniotic and allantoic fluid Cu concentrations were significantly negative, while the relationship between age of the fetus and maternal plasma, fetal liver, amniotic fluid, allantoic fluid and fetal kidney Cu concentrations were significantly positive may indicate that, the dam and fetus depend on the maternal liver Cu contents during gestation and it can be used as an indicator of the Cu status through gestation and fetuses have a capacity to sequester maternal Cu, even when the dam is Cu deficient (Graham et al, 1994). Parkinson et al (1981) found that amniotic fluid copper concentration gradually increased during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…This approach can lead to unnecessary expense with no appreciable decrease in disease prevalence and, occasionally, poisoning. 2,5,8,17,20,22,24,25 Supplementation of cattle with intrareticular copper boluses at label doses is reported to be safe and effective. 4,6,21 Epidemiologic and pathologic features of chronic copper intoxication of suckling calves improperly supplemented with intrareticular copper boluses are documented in this report.…”
mentioning
confidence: 99%
“…Poisoning with these boluses was reported in Nebraska and Wyoming, but descriptive features and epidemiologic details were limited. 8 A 410-cow crossbred beef cattle operation in North Dakota experienced an increase in calf mortality during the summer of 1993. Received for publication September 7, 1996. was not observed, and abdominal pain was suspected to be responsible for this behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation